CONCEPT OF DIGITALIS ACTION - MENDEZ, RAFAEL (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1973)
Intracavity potentials were studied in the dog's heart When various arteries are ligated either positive or negative S-T shifts are found In the case of premature beats, a strikingly similar appearance in the pattern of intracavity potential of right ve
ARCH INST CARDIOL MEX
Keywords: CONCEPT, DIGITALIS; CIENCIAS MEDICAS; MEDICINA INTERNA; CARDIOLOGIA